2010
DOI: 10.1029/2009jd013216
|View full text |Cite
|
Sign up to set email alerts
|

Size‐segregated measurements of cloud condensation nucleus activity and hygroscopic growth for aerosols at Cape Hedo, Japan, in spring 2008

Abstract: [1] Size-segregated measurements of cloud condensation nucleus (CCN) activity and hygroscopic growth were performed simultaneously for sulfate-rich aerosols at Cape Hedo, Okinawa, Japan, in spring 2008. The CCN fractions as functions of particle size at water vapor supersaturations of 0.44%, 0.25%, and 0.10% had nearly stepwise increases, and the diameters for 50% activation of its maximum (d act ) were close to that of (NH 4 ) 2 SO 4 . The size-resolved hygroscopic growth factor g measured using a hygroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 93 publications
(105 reference statements)
8
85
2
Order By: Relevance
“…The mean organic mass fraction of 0.49 was larger than that of Jeju Island (0.41; Topping et al, 2004), Okinawa Island (0.17 to 0.20;Takami et al, 2007;Miyoshi et al, 2013). This result is consistent with the smaller κ values as compared to those of Jeju Island and Okinawa Island (Mochida et al, 2010). The mean organic mass fraction was comparable with that for Fukue Island (0.45; Takami et al, 2005).…”
Section: Chemical Characteristics Of Nr-pmsupporting
confidence: 80%
See 3 more Smart Citations
“…The mean organic mass fraction of 0.49 was larger than that of Jeju Island (0.41; Topping et al, 2004), Okinawa Island (0.17 to 0.20;Takami et al, 2007;Miyoshi et al, 2013). This result is consistent with the smaller κ values as compared to those of Jeju Island and Okinawa Island (Mochida et al, 2010). The mean organic mass fraction was comparable with that for Fukue Island (0.45; Takami et al, 2005).…”
Section: Chemical Characteristics Of Nr-pmsupporting
confidence: 80%
“…However, the κ CCN values were clearly smaller than those of previous studies in East Asia. The previously reported values such as 0.49 ± 0.09 for Jeju Island, Korea and 0.50 ± 0.05 for Okinawa Island, Japan (Mochida et al, 2010) were closer to the value of κ of pure (NH 4 ) 2 SO 4 (0.61; Petters and Kreidenweis, 2007). Note that κ CCN values at other sites were calculated by the same method as used in this study, using the CCN activation diameter reported in the literature Mochida et al, 2010).…”
Section: Averaged Ccn Efficiency Spectra and Related Parametersmentioning
confidence: 89%
See 2 more Smart Citations
“…Hereafter, the CCNC-derived d act and σ are expressed as d act , CCN and σ CCN , respectively. The SS in the CCNC was calculated to be 0.18%, 0.49%, and 0.95% from d act,CCN of ammonium sulfate particles, using the Köhler equation and incorporating the Pitzer model as described by Mochida et al [2010].…”
Section: Calibration and Data Processingmentioning
confidence: 99%